2006
DOI: 10.1021/jp064893e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nitrogen-Substituted TiO2 Thin Film Photocatalysts by the Radio Frequency Magnetron Sputtering Deposition Method and Their Photocatalytic Reactivity under Visible Light Irradiation

Abstract: Nitrogen-substituted TiO2 (N-TiO2) thin film photocatalysts have been prepared by a radio frequency magnetron sputtering (RF-MS) deposition method using a N2/Ar mixture sputtering gas. The effect of the concentration of substituted nitrogen on the characteristics of the N-TiO2 thin films was investigated by UV-vis absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses. The absorption band of the N-TiO2 thin film was found to shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
150
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 43 publications
11
150
0
1
Order By: Relevance
“…A similar spectroscopic feature was observed for TiO 2 doped with Cr and N prepared by physical methods such as ion implantation and magnetron sputtering. [10,35] In contrast, on chemically doping Cr and N ions into TiO 2 , fairly strong shoulders by the d-d transition appear in the visible region with the absorption edge almost invariant. [12] Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar spectroscopic feature was observed for TiO 2 doped with Cr and N prepared by physical methods such as ion implantation and magnetron sputtering. [10,35] In contrast, on chemically doping Cr and N ions into TiO 2 , fairly strong shoulders by the d-d transition appear in the visible region with the absorption edge almost invariant. [12] Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…For this purpose, doping of metal ions and anions into TiO 2 has been intensively studied. [6][7][8][9][10][11][12] However, the defects introduced into TiO 2 lead to a decrease in its crystallinity reducing the carrier mobility and increasing the recombination probability. Consequently, if visible-light activity is obtained, the UV-light activity decreases in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…This research found that the presence of nitrogen in the structure of TiO2 as substitution by oxygen creates Ti-N bonds and electronic states in forbidden energy levels [12,13]. This anionic partial substitution increases the range of the solar spectrum absorbed [14]. In this case, nanoparticles of TiOxNy can absorb wavelengths between 365 nm and 500 nm [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…11 Given the current state-of-art, 5,[12][13][14] it is highly desirable to identify new synthesis routes for TiO 2 doping in order to obtain visible light-active photocatalysts. TiO 2 , doped or not, has been synthesized using techniques such as sputtering, 15,16 chemical vapor deposition, 17,18 sol-gel process, 19,20 hydrothermal process, 7 electrochemical methods, 21,22 and, more recently, ionothermal synthesis. 23,24 Ionothermal synthesis was referred for the first time in 2004 by Cooper et al 25 to distinguish the synthesis carried out using solvents composed predominantly by ionic liquids (IL) or deep eutectic mixtures (EU) from hydrothermal preparations, which take place in a predominantly molecular solvent.…”
Section: Introductionmentioning
confidence: 99%